Institutional Narrative of Digital Transformation: Toward an Educational Innovation Management Model to Enhance Higher Education Competitiveness - Wakidi Wakidi; Fatimah Aristiati; Ayuba Olaniyi Jibril (International Journal of Educational Narratives, 2026)
Background: The development of digital technology has encouraged higher education institutions to innovate in their learning systems and institutional governance to increase competitiveness. Various studies have addressed the adoption of digital technology in education, but a clear gap remains regarding the lack of integrated, systematic, and contextual innovation management that links the use of digital technology with increased higher education competitiveness. Purpose: This study aims to analyze the Institutional Narrative of Digital Transformation: Towards an Educational Innovation Management Model to Enhance the Competitiveness of Higher Education Institutions. Method: This research employs a qualitative approach with conceptual and narrative analysis of the literature on digital transformation, educational innovation, and institutional competitiveness. The data sources are scientific publications relevant to the research topic. Data collection techniques include a systematic literature search using scientific databases. Conclusion: Digitalization technology must be realized as a transformation encompassing changes in work processes, interaction patterns, and data-driven decision-making. This process must be gradual and sustainable, starting with vision, capacity building, system integration, monitoring, and adaptation. This integrated process will excel in efficiency, innovation, and global competitiveness, becoming a strategic step for the institution's future.